The Role of Local Culture in North Sumatra in Improving Mathematical Ability in the Learning of Space Shapes for 5th Grade Elementary School Students - Ansya, Yusron Abda’u; Salsabilla, Tania; Mailani, Elvi (Jurnal Ilmu Manajemen dan Pendidikan, 2024)
This research aims investigates the role of North Sumatra's local culture in enhancing fifth-grade students’ mathematics skills, focusing on spatial geometry. The research addresses the issue of students’ low comprehension of spatial concepts in mathematics, highlighting the need for innovative approaches connected to everyday life. Using a qualitative case study method, the research involved fifth-grade students and teachers at SD Muhammadiyah 29 Sunggal and was conducted from July to September 2024.Findings reveal that incorporating local cultural elements into mathematics learning significantly improves students’ understanding and interest. By integrating examples like Batak traditional houses and Maimun Palace, students better grasp abstract geometric concepts by connecting them to familiar objects. This approach transforms abstract ideas into concrete and relatable learning experiences, facilitating comprehension. Observations and interviews indicate that students responded enthusiastically, actively participating in lessons and showing greater motivation to engage with mathematics. This method not only strengthens their spatial understanding but also enriches their educational experience by embedding valuable cultural knowledge. Thus, integrating local cultural contexts into mathematics education proves to be an effective strategy for improving learning outcomes while fostering appreciation for cultural heritage.